2015
DOI: 10.1017/jmo.2014.65
|View full text |Cite
|
Sign up to set email alerts
|

Do environment and intuition matter in the relationship between decision politics and success?

Abstract: Little is known about the relationship between political behavior and successful decision making in non-Western national settings, or about the impact of environmental factors on this relationship. Moreover, our understanding of the decision processes through which political behavior translates into decision outcomes is also not well understood. The present research extends previous studies by examining how political behavior influences decision success in a new setting, with reference to the moderating impact… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
25
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 31 publications
(27 citation statements)
references
References 60 publications
(119 reference statements)
2
25
0
Order By: Relevance
“…More and more organisations are adopting the project management method in their management. Recent research has shown the important role of team intuition and reflexivity in project management (Baldacchino, 2013;Elbanna et al, 2015). The present study extends and develops this emerging research by using a model of technological uncertainty and technical complexity, project managers' intuitive decision making, the use of reflexivity and project performance in order to examine the impact on project planning.…”
Section: Discussionmentioning
confidence: 83%
See 3 more Smart Citations
“…More and more organisations are adopting the project management method in their management. Recent research has shown the important role of team intuition and reflexivity in project management (Baldacchino, 2013;Elbanna et al, 2015). The present study extends and develops this emerging research by using a model of technological uncertainty and technical complexity, project managers' intuitive decision making, the use of reflexivity and project performance in order to examine the impact on project planning.…”
Section: Discussionmentioning
confidence: 83%
“…Studies were limited to understanding the antecedent of intuition. The role of intuition in other processes is poorly understood by managers and academic researchers like (Elbanna et al, 2015). Hence research investigating the effect of intuition on project processes will be highly helpful.…”
Section: Intuitionmentioning
confidence: 99%
See 2 more Smart Citations
“…Yet, for years research in this area was non-existent, and to date it still is relatively scarce. Two recent studies focused on the interplay between intuitive and political decision-making (Brinkerink and Bammens, 2018;Elbanna et al, 2015), three studies focused on the interlinkages between rational and intuitive decision-making (Calabretta et al, 2017;Kester et al, 2009;Skrepnek and Sarnowski, 2007), and two research project studied rational, intuitive and political decision-making in conjunction (Behrens, 2016;Stanczyk et al, 2015).One element that remains understudied, also in the above-mentioned research, is the dynamic aspect. Research has not addressed the question whether and how the use of these decision-making dimensions in innovation processes changes over time.…”
mentioning
confidence: 99%